Integrasi Smart Apps Creator dalam Media Pembelajaran Interaktif Berbasis Android untuk Meningkatkan Kemampuan Literasi Numerasi Siswa - Ningtiyas, Fitri Ayu; Mahmuzah, Rifaatul (Pusat Studi Pengembangan Pembelajaran Matematika Sekolah UIN Sunan Kalijaga Yogyakarta Jl. Marsda Adisucipto, Yogyakarta 55281, 2025)
Mathematics education plays an important role in shaping students' logical, critical, and systematic thinking skills. One indicator of the success of mathematics education can be seen from students' numeracy literacy skills, this study intends to review the improvement of students' numeracy literacy skills through Android-based interactive learning integrated with Smart Apps Creator. This study used a quasi-experimental method with a nonequivalent control group design involving class X-2 as the experimental class and X-3 as the control class at SMA Negeri 1 Dewantara. Data were collected through pretest and posttest and analyzed using a two-sample t-test. The results mentioned that there was a significant increase in students' numeracy literacy skills in the experimental class compared to the control class, with an average n-gain score of the experimental class being higher. Furthermore, normality and homogeneity tests were carried out before testing the hypothesis of the 2-sample t-test. Based on the results of the tests carried out, information was obtained that the data were normally distributed and homogeneous. Hypothesis testing produced a significance value < 0,05. It can be concluded that android-based interactive learning media integrated with Smart Apps Creator is effective in improving students' numeracy literacy skills. These findings indicate that the use of android-based learning media can be an effective strategy in supporting learning in the digital era. This media provides more flexible, interactive learning access, and is able to increase student involvement in the learning process.